Analysis of Student Activity in Learning Thermochemical Materials through Lesson Study - Eny Winaryati; Muhammad Agung Stiarso; Endang Tri Wahyuni; Muhammad Taufik Hidayat; Wahono Wahono (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
Lesson study is a learning strategy that emphasizes collaborative activities on planning (plan), implementation of learning (do), and reflection, with the aim of improving the quality of learning, so that students' learning activities and student learning outcomes become good. The purpose of this study is to analyze the activity and student learning outcomes through lesson study. Activities carried out in 3 (three) cycles. Based on the results of reflection and decisions taken by the model teacher, resulting in the application of different learning models from each cycle. It was concluded that in cycle 1 applying the demonstration method, cycle 2 of the Teams Game Tournament (TGT) learning model, cycle 3 applying the TGT model combined with the LCC method. The learning process with the implementation of Lesson Study in Thermochemical material can improve the activity and learning outcomes in the XI IPA class of SMA Muhammadiyah Gubug, Grobogan Regency, 2018/2019 school year. The recommendations of this study are the need for application of other methods in learning Thermochemical content, and comparing their effectiveness. Key word: Lesson Study, Activity, Thermochemistry